Preventing within household transmission of Covid-19: is the provision of accommodation to support self-isolation feasible and acceptable? - Sarah Denford; Kate Morton; Jeremy Horwood; Rachel de Garang; Lucy Yardley (BMC, 2021)
Abstract Background Within-household transmission of Covid-19 is responsible for a significant number of infections. Efforts to protect at risk communities are needed. This study explored the acceptability of offering accommodation to support self-isolation among at risk populations, to prevent transmission of Covid-19 within vulnerable households. Methods Mixed methods design structured in two phases. Phase 1: Survey of 545 individuals who had provided consent to be contacted about ongoing research projects into infection control. Phase 2: Semi-structured interviews with 19 participants from ethnic minority and low income communities. Results Many survey and interview participants viewed the provision of accommodation as important and necessary in certain contexts. Of the 110 survey respondents, 85 (77%) said that they were not able to isolate at home. Among this group, 24 (28%) said they would accept accommodation and 23 (27%) said that they would probably accept. Of those unable to isolate at home, and at high risk if they caught the virus (N = 36) or living with someone at high risk (N 18), 19 (35%) said that they would accept, and 12 (22%) said they would probably accept accommodation. Factors influencing uptake of accommodation included perceived 1) household vulnerability 2) virus exposure and 3) lack of isolation at home options. Barriers to accepting the accommodation offer included 1) able to isolate at home 2) wanting to be with family 3) caring responsibilities 4) mental wellbeing concerns 5) concerns about moving when ill and 6) infection control concerns. Participants raised issues that should be addressed before accommodation is offered, including questions regarding who should use temporary accommodation and when, and how infection control in temporary accommodation would be managed. Conclusion The provision of accommodation to prevent within household transmission of Covid-19 is viewed as acceptable, feasible and necessary by some people who are concerned about infection transmission in the home and are unable to self-isolate or socially distance at home. Different households will have different requirements, e.g., those with caring responsibilities, and to overcome these challenges additional support may be needed for the provision of accommodation to be feasible to those who could benefit most.